Pole piece, battery and electric device

CN123017966APending Publication Date: 2026-10-30BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510578546.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但碳纳米管分散难度高,无法发挥其长径比和力学强度高的特点,应用在电池中时,无法有效降低电池电阻,提高电池的导电性能

Benefits of technology

[0007]本申请实施例第二方面提供了一种电池,包括本申请实施例第一方面所述的极片。由于带有本申请实施例第一方面提供的极片,该电池可降低电池内阻,提升电池的导电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a pole piece, a battery and an electric device, which comprise carbon nanotubes and MXene materials, and the mass ratio of the MXene materials to the carbon nanotubes is (0.1-10):1. By adding the MXene materials and the carbon nanotubes to the pole piece, the mass ratio of the MXene materials to the carbon nanotubes is optimized (0.1-10):1, the high conductivity and high dispersibility characteristics of the MXene materials are fully exerted, the MXene materials are used to assist in dispersing the carbon nanotubes, the internal resistance of the battery is reduced, and the conductivity of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to an electrode, a battery, and an electrical device. Background Technology

[0002] Secondary batteries are widely used in electric vehicles, electric motorcycles, aerospace and other fields, and the demand for compaction density of secondary batteries in these fields is gradually increasing.

[0003] In existing systems, carbon nanotubes are typically added to the electrode slurry system to improve the conductivity of the electrode. However, carbon nanotubes are difficult to disperse, and their high aspect ratio and mechanical strength cannot be fully utilized. Therefore, when applied to batteries, they cannot effectively reduce battery resistance and improve battery conductivity. Summary of the Invention

[0004] In order to at least solve the problems existing in the prior art, this application provides an electrode, a battery, and an electrical device.

[0005] The first aspect of this application provides an electrode sheet including a conductive agent, which includes a first conductive agent comprising MXene material and carbon nanotubes, wherein the mass ratio of MXene material to carbon nanotubes is (0.1-10):1.

[0006] This application optimizes the mass ratio of MXene material and carbon nanotubes (0.1-10):1 by adding MXene material and carbon nanotubes to the electrode, thereby fully leveraging the high conductivity and high dispersibility of MXene material. The use of MXene material to assist in the dispersion of carbon nanotubes reduces the internal resistance of the battery and improves its conductivity.

[0007] A second aspect of this application provides a battery including the electrode sheet described in the first aspect of this application. Due to the presence of the electrode sheet provided in the first aspect of this application, the battery can reduce its internal resistance and improve its conductivity.

[0008] A third aspect of this application provides an electrical device including the battery provided in the second aspect of this application. Due to the use of the battery provided in this application, the electrical device has a promising market prospect. Detailed Implementation

[0009] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0010] The first aspect of this application provides an electrode sheet comprising a conductive agent, the conductive agent comprising a first conductive agent comprising carbon nanotubes and MXene material, wherein the mass ratio of MXene material to carbon nanotubes is (0.1-10):1.

[0011] Specifically, MXene is a novel two-dimensional conductive material with excellent conductivity, which is beneficial for improving the conductivity of electrodes. The surface of MXene contains abundant functional groups, which helps to form a more stable SEI film. Furthermore, MXene exhibits superior dispersion in aqueous solvents. Controlling the mass ratio of MXene to carbon nanotubes within the range of (0.1-10):1 can assist in the dispersion of carbon nanotubes, improving battery conductivity and reducing internal resistance. Improved battery conductivity is beneficial for enhancing cycle performance and compaction density. The two-dimensional nature of MXene can promote the slippage of the active material, further increasing the battery's compaction density. The specific mass ratio of MXene to carbon nanotubes can be 0.1:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any combination thereof.

[0012] The electrode provided in this application includes carbon nanotubes and MXene material, with a mass ratio of MXene material to carbon nanotubes of (0.1-10):1. This has the following effects: by adding MXene material and carbon nanotubes to the electrode and optimizing the mass ratio of MXene material to carbon nanotubes to (0.1-10):1, the high conductivity, high mechanical strength and high dispersibility of MXene material are fully utilized. Using MXene material to assist in dispersing carbon nanotubes can improve the cycle performance and compaction density of the battery and reduce the internal resistance of the battery.

[0013] In the embodiments of this application, the electrode can be a positive electrode or a negative electrode. When the electrode is a positive electrode, it includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The first conductive agent described in this application can be located on the positive current collector and / or in the positive active material layer. Similarly, when the electrode is a negative electrode, it includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. The first conductive agent described in this application can be located on the negative current collector and / or in the negative active material layer.

[0014] Specifically, the mass ratio of MXene material to carbon nanotubes can be determined by the following method: The electrode is placed in an HCl solution of a certain concentration, and the dissolution process is accelerated by stirring or ultrasonic treatment to remove the foil, binder, thickener, and SEI and CEI films from the electrode. The solution and insoluble components are then separated by filtration or centrifugation. The insoluble components are dried and ground into fine particles of a certain size, then mixed with an appropriate amount of solvent or dispersant, and placed in an ultrasonic bath or ultrasonically treated using an ultrasonic probe to form a uniform suspension. During ultrasonic treatment, due to the different properties of carbon nanotubes and MXene material, slight aggregation and dispersion phenomena occur. After ultrasonication, the sample is centrifuged. Adjusting the centrifugation rate allows for the separation of MXene material, carbon nanotubes, and the main material, which are then subjected to separate property tests.

[0015] In some preferred embodiments, the mass ratio of MXene material to carbon nanotubes is (0.2-2):1.

[0016] Specifically, within this mass ratio of MXene material to carbon nanotubes, the mesh support structure of carbon nanotubes can be utilized to further balance the conductivity and strength of the electrode.

[0017] In some embodiments, the particle size Dv50 of the MXene material is 0.1 μm-5 μm.

[0018] Specifically, the particle size Dv50 of MXene material can be, but is not limited to, a range of 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, or any combination thereof. Particle size Dv50 refers to the particle size corresponding to a cumulative volume percentage of MXene material particles reaching 50%. MXene material can be separated using the method described above and measured using a Malvern particle size analyzer. MXene material with a particle size within the aforementioned range can more fully utilize its high conductivity and high dispersibility, further reducing battery resistance.

[0019] In some embodiments, the general formula of MXene materials is M n+1 X n Tx, where n = 1, 2, 3, M is a transition metal, X is carbon or nitrogen, and Tx is a -O, -F, or -OH group.

[0020] Specifically, carbon or nitrogen forms strong covalent bonds (such as Ti-C bonds) with transition metals (such as Ti), providing high electron mobility (~10^3). 4The S / m ratio significantly improves the electronic conductivity of the electrode. Furthermore, its embedding within the transition metal layers ensures the structural stability of the MXene material. Functional groups such as -OH, -F, and -O impart hydrophilicity to the MXene material, improving the dispersibility of the electrode slurry and preventing agglomeration.

[0021] In some preferred embodiments, M is at least one selected from Ti, Zr, Hf, V, Nb, Ta, Cr, Sc, and Mo. Specifically, selecting at least one of the above-mentioned metallic elements can result in better conductivity and dispersion properties. In some embodiments of this application, the MXene material includes at least one selected from Ti3C2Tx, V2CTx, and Nb2CTx. Ti3C2Tx, V2CTx, and Nb2CTx have excellent conductivity and capacity, and when applied in batteries, they can improve the cycle performance and conductivity of the batteries.

[0022] In some embodiments, the thickness L of the MXene material is 1 nm to 10 nm.

[0023] Specifically, the thickness L of the MXene material can be, but is not limited to, a range of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any combination thereof. The thickness L of the MXene material refers to the dimension of the MXene material in the unit stacking direction, which can be measured using scanning electron microscopy (SEM) or transmission electron microscopy (TEM) according to the methods in GB / T30544.13-2018. Within the above-mentioned range, the thickness L of the MXene material can further promote carbon nanotube dispersion and active host material slippage, thereby increasing the compaction density of the battery.

[0024] In some embodiments, carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0025] Specifically, single-walled carbon nanotubes and multi-walled carbon nanotubes have high aspect ratios. Adding a small amount to the electrode can form a three-dimensional conductive network with excellent conductivity, as well as high elastic modulus and tensile strength, which helps to improve the flexibility and mechanical strength of the electrode.

[0026] In some embodiments, the diameter of the carbon nanotubes is 1 nm-40 nm.

[0027] Specifically, the diameter of carbon nanotubes refers to their outer diameter, which can be measured using scanning electron microscopy (SEM) or transmission electron microscopy (TEM) according to the methods in GB / T30544.13-2018. Carbon nanotubes within this diameter range exhibit superior electrical conductivity and mechanical properties, higher electron transport rates, and provide structural support for the electrode, balancing conductivity and strength. The diameter of carbon nanotubes can be, for example, but not limited to, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, or any combination thereof.

[0028] In some embodiments, the conductive agent further includes a second conductive agent, which includes at least one of carbon black, graphene, and carbon fiber materials.

[0029] Specifically, adding conductive agents other than MXene materials and carbon nanotubes to the negative electrode, such as at least one of carbon black, graphene, and carbon fiber materials, can further enhance the conductivity of the electrode.

[0030] In some embodiments, the electrode includes a negative electrode.

[0031] Specifically, the electrode described in this application can be either a positive electrode or a negative electrode, or both the positive and negative electrode may contain the conductive agent described in this application. Preferably, the electrode in this application is a negative electrode, and the negative electrode containing the conductive agent described in this application can better improve the conductivity of the battery and reduce the internal resistance of the battery.

[0032] In some embodiments, the negative electrode sheet includes a negative current collector and a negative active layer disposed on at least one side of the negative current collector, the negative active layer including the conductive agent.

[0033] Specifically, when the electrode described in this application is a negative electrode, the negative electrode includes a negative current collector and a negative active layer disposed on at least one side of the negative current collector, the negative active layer including the conductive agent; it may have negative active layers on both sides of the negative current collector, the negative active layer on at least one side including the conductive agent described in this application, or it may have a negative active layer on one side of the negative current collector, the negative active layer including the conductive agent described in this application.

[0034] In some embodiments, the negative electrode active layer includes a negative electrode active material, wherein the negative electrode active material includes a silicon-based negative electrode active material.

[0035] Specifically, silicon-based anode active materials can improve the compaction density of the battery. Applying MXene materials to silicon-based anodes helps to suppress the volume expansion of silicon-based anode active materials, thereby further improving the battery's capacity and cycle performance.

[0036] In some embodiments, the silicon-based anode active material includes at least one of silicon, silicon alloy, silicon-oxygen material, silicon-carbon material, and silicon-oxygen-carbon material.

[0037] Specifically, silicon-based anode active materials selected from at least one of silicon, silicon alloys, silicon-oxygen materials, silicon-carbon materials, and silicon-oxygen-carbon materials can further improve the compaction density and cycle performance of the battery.

[0038] In some embodiments, the conductive agent accounts for 0.1%-3% of the mass of the negative electrode active layer.

[0039] Specifically, the mass percentage of the conductive agent in the negative electrode active layer can be, but is not limited to, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any combination thereof. When the mass percentage of the conductive agent in the negative electrode active layer is within this range, the negative electrode sheet has good conductivity. The structure of the negative electrode sheet can be controlled by adjusting the proportion of the added conductive agent, thereby improving the transport performance of active ions.

[0040] In some embodiments, the negative electrode active layer includes a plurality of sub-negative electrode active layers, and at least one sub-negative electrode active layer includes the aforementioned conductive agent.

[0041] Specifically, the negative electrode sheet provided in this application can be a multilayer coated negative electrode sheet, including multiple sub-negative electrode active layers. The number of sub-negative electrode active layers can be two, three, four, etc., wherein at least one sub-negative electrode active layer includes the aforementioned conductive agent. The pore structure of the electrode sheet is adjusted by adding the conductive agent of this application to one or more of these layers.

[0042] In detail, each sub-negative electrode active layer may contain the aforementioned conductive agent, or a portion of the sub-negative electrode active layer may contain the conductive agent while the remaining sub-negative electrode active layers do not. Specifically, electrode slurries containing and without the aforementioned conductive agent can be prepared separately, and, depending on actual needs, the electrode slurries containing and without the aforementioned conductive agent can be used to coat at least one side of the current collector.

[0043] In some embodiments, the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer, the second negative electrode active layer being disposed between the negative electrode current collector and the first negative electrode active layer, and the first negative electrode active layer including the conductive agent.

[0044] Specifically, by adding the conductive agent of this application to the negative electrode active layer near the electrolyte side, the pore structure of the first negative electrode active layer can be controlled, thereby improving the conductivity and cycle performance of the electrode.

[0045] In some embodiments, the conductive agent of the second negative electrode active layer is a second conductive agent and / or carbon nanotubes.

[0046] Specifically, by adding the conductive agent of this application to the negative electrode active layer near the electrolyte and adding a conventional conductive agent to the second negative electrode active layer near the current collector, the overall pore structure of the electrode can be controlled, the wettability of the electrolyte can be increased, and the conductivity and cycle performance of the electrode can be improved.

[0047] In some embodiments, the porosity of the first negative electrode active layer is greater than that of the second negative electrode active layer.

[0048] Specifically, the porosity of the first negative electrode active layer near the electrolyte is greater than that of the second negative electrode active layer near the negative electrode current collector. This can increase the wetting of the electrode by the electrolyte, build a high-speed channel for active ion transport, and balance the battery's compaction density and fast charging capability.

[0049] The negative electrode current collector in this embodiment can be a conventional negative electrode current collector in the art, for example, the negative electrode current collector includes copper foil. Preferably, the negative electrode current collector includes carbon-coated copper foil.

[0050] In some embodiments, the negative electrode active layer may further include an adhesive. The adhesive in the negative electrode active layer may be any adhesive suitable for negative electrodes known in the art. For example, the adhesive in the negative electrode active layer includes at least one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), tetrafluoroethylene and its copolymers, polyvinylidene fluoride and its copolymers, polyolefins and their copolymers (e.g., polyethylene-polyethylene glycol block copolymers), polyethers and their copolymers (e.g., polyethylene oxide), polyphenylene ethers and their copolymers, polysiloxanes and their copolymers (e.g., polydimethylsiloxane, poly(dimethylsiloxane-co-alkylmethylsiloxane)), polyesters and their copolymers (e.g., polyethylene ester, polyvinyl acetate, polyacrylate, etc.), carboxymethyl cellulose, styrene-butadiene latex, nitrile rubber, and polyacrylic acid (PAA). Specifically, polyolefins include one or more of polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / vinylidene fluoride copolymer, and propylene / vinylidene fluoride copolymer; polytetrafluoroethylene and its copolymers may be at least one of tetrafluoroethylene / ethylene copolymer, tetrafluoroethylene / propylene copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, tetrafluoroethylene / ether copolymer, tetrafluoroethylene / branched polyether copolymer, tetrafluoroethylene / vinyl ether copolymer, tetrafluoroethylene / branched polyether / vinyl ether copolymer, and tetrafluoroethylene / siloxane copolymer.

[0051] In the embodiments of this application, the negative electrode sheet can be prepared by a dry process (i.e., rolling the material used to form the negative electrode active layer into a film and then combining it with the negative electrode current collector to obtain the negative electrode sheet), or by a wet process (coating method) (i.e., coating the negative electrode slurry used to form the negative electrode active layer onto the surface of the negative electrode current collector, and then drying, rolling and other processes to form the negative electrode active layer on the surface of the negative electrode sheet to obtain the negative electrode sheet).

[0052] The second aspect of this application provides a battery including the electrode sheet described in the first aspect, which can reduce battery resistance and improve battery conductivity, compaction density and cycle performance.

[0053] The battery of this application includes a positive electrode and a negative electrode, both of which can be the electrode described in the first aspect of this application.

[0054] When the electrode in this application is a positive electrode, the positive electrode includes a positive current collector and a positive active layer located on at least one side surface of the positive current collector. Specifically, the positive active layer can be provided on one side surface in the thickness direction of the positive current collector, or positive active layers can be provided on both opposite sides surface in the thickness direction of the positive current collector.

[0055] Specifically, the positive electrode active layer may include a positive electrode active material, a conductive agent, and a binder. In the positive electrode active layer, the mass percentage of the positive electrode active material may be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99%, or any combination thereof. The mass fraction of the binder may be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15%, or any combination thereof.

[0056] In this embodiment, the binder in the positive electrode active layer can be a conventional adhesive material in the art. For example, the binder in the positive electrode active layer may include one or more of the following: polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc.

[0057] In some embodiments of this application, the positive electrode active layer may further include at least one of functional additives such as dispersants, stabilizers, and leveling agents. The embodiments of this application do not impose specific limitations on the mass percentage content of the above reagents; selection can be made according to actual conditions. In some embodiments, the mass percentage content of the above functional additives in the positive electrode active material may be 0.1% to 15%.

[0058] The embodiments of this application may employ conventional positive current collectors in the art, for example, positive current collectors may include aluminum foil.

[0059] In this embodiment, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the positive electrode active material, conductive agent, binder, and other components used to form the positive electrode active layer can be dispersed in a solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry. This slurry is then coated onto the surface of the positive electrode current collector, and after drying, rolling, and other processes, the positive electrode sheet is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing positive electrode sheets using the coating method, and are not particularly limited thereto.

[0060] In some embodiments, the battery described above can be a lithium-ion battery or a sodium-ion battery.

[0061] In some embodiments, the battery is a lithium-ion battery, and the positive electrode active material may include LiCoO2, LiNiO2, or LiCo. x Ni 1-x O2 (0≤x≤1), LiCo x Ni 1-x-y Al y O2(0≤x≤1,0≤y≤1), LiMn2O4, LiFe x Mn y M z O4 (M is one or more of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn or Mo, 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), Li 1+x L 1-y-z M y N z O2 (L, M, N are one or more of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S, B, -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1), LiFePO4, Li3V2(PO4)3, Li3V3(PO4)3, LiVPO4F, Li2CuO2, Li5FeO4, and metal sulfides and oxides (such as TiS2, V2S3, FeS, FeS2, LiMS) x (M is at least one of the transition metal elements such as Ti, Fe, Ni, Cu, Mo, etc., 1≤x≤2.5), TiO2, Cr3O8, V2O5, MnO2, etc.

[0062] When the battery is a sodium-ion battery, the positive electrode active material includes, but is not limited to, one or a combination of transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue materials.

[0063] Generally, a battery includes an electrolyte, a battery cell, and a casing that encapsulates the battery cell. The electrolyte is injected into the battery cell inside the casing. The battery cell includes a positive electrode, a negative electrode, and a separator located between the positive and negative electrode. The battery cell can be a stacked cell, meaning it is composed of alternating layers of positive electrode, separator, and negative electrode; or it can be a wound cell, meaning it is composed of stacked positive electrode, separator, and negative electrode, which are then wound together.

[0064] The electrolyte in this application embodiment can be a conventional electrolyte in the art. For example, the electrolyte is a non-aqueous electrolyte, which may specifically include organic solvents, additives and electrolyte salts. Organic solvents include one or more of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC). Additives include, for example, fluoroethylene carbonate (FEC) and vinylene carbonate (VC). Electrolyte salts may include lithium salts, such as lithium hexafluorophosphate (LiPF6), but are not limited thereto.

[0065] In this embodiment, the separator is used to separate the positive and negative electrode plates, preventing short circuits caused by contact between them. Conventional separators in the art can be used in this embodiment, and there are no particular limitations. For example, one or more materials selected from polyethylene, polypropylene, and polyvinylidene fluoride can be used as the separator.

[0066] In this embodiment, the battery cell can be packaged using conventional housing materials in the art, such as flexible packaging materials like aluminum-plastic film, but is not limited to these.

[0067] The embodiments of this application can assemble components such as positive electrode sheets, separators, and negative electrode sheets into a battery using conventional methods in the art. For example, positive electrode sheets, separators, and negative electrode sheets can be stacked alternately to obtain a stacked battery cell (or wound into a wound battery cell); then the battery cell is placed in a casing (outer packaging), and after conventional processes such as electrolyte injection and encapsulation, a battery is obtained. In a specific implementation, artificial graphite, the above-mentioned conductive agent, thickener (CMC), and binder (SBR) of the negative electrode active material can be mixed in a mass ratio of 96:1:2:0.5, and the powder and deionized water can be stirred into a negative electrode slurry using a homogenizer and uniformly coated onto copper foil.

[0068] The positive electrode active material lithium iron phosphate (LiFePO4), conductive agent (CNT), and binder (PVDF) are mixed in a mass ratio of 97:1:2. The powder and NMP are then stirred into a positive electrode slurry using a homogenizer and uniformly coated onto aluminum foil.

[0069] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1, and 1M LiPF6 was added to prepare an electrolyte containing 1M LiPF6.

[0070] The battery of this application may be in the form of a battery cell, a battery module, or a battery pack. In some embodiments, battery cells may be assembled into a battery module, and the number of battery cells contained in a battery module may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery module. In some embodiments, battery modules may also be assembled into a battery pack, and the number of battery modules contained in a battery pack may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery pack.

[0071] The specific type of battery in this application is not particularly limited. For example, from the perspective of shape, the battery includes, but is not limited to, prismatic batteries, pouch batteries, and cylindrical batteries, etc., and this application does not impose any particular restrictions. From the perspective of the core structure, the core of the battery can be a wound core (i.e., the core is formed by winding after the positive electrode sheet, negative electrode sheet, and separator are stacked). It can also be a stacked core (i.e., multiple positive electrode sheets, negative electrode sheets, and separators are stacked to form the core).

[0072] A third aspect of this application also provides an electrical device including the aforementioned battery. By using the aforementioned battery in the electrical device, electrical energy can be continuously and stably output to supply the electrical device, resulting in a longer service life for the electrical device. At the same time, it can also reduce the maintenance of the battery in the electrical device, which is beneficial for saving costs.

[0073] The electrical equipment provided in this application can be conventional electrical equipment in the field, such as power equipment (e.g., electric vehicles), electrical equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without any particular limitation.

[0074] The present application will be further described in detail below through examples.

[0075] Example 1

[0076] This embodiment illustrates the negative electrode sheet and battery disclosed in this application, and includes the following steps:

[0077] (1) Preparation of negative electrode sheet: The negative electrode active material silicon-carbon material, conductive agent, thickener (CMC), binder (SBR), and toughening agent (PAA) are mixed in a ratio of 96:1:1:1:1. The powder and deionized water are stirred into a negative electrode slurry using a homogenizer and uniformly coated onto copper foil. After rolling, the negative electrode sheet of the battery is obtained. The conductive agent is MXene material (specifically Ti3C2Tx) and single-walled carbon nanotubes. The Dv50 of MXene material is 0.5 μm, and the mass ratio of MXene material to single-walled carbon nanotubes is 0.5:1.

[0078] (2) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate LiFePO4, conductive agent (conductive carbon black SP) and binder (PVDF) are mixed in a ratio of 97:1:2. The powder and NMP are stirred into a positive electrode slurry in a homogenizer and uniformly coated on aluminum foil. After rolling, the positive electrode sheet of the battery is obtained.

[0079] (3) Preparation of electrolyte: Ethyl carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 to prepare an electrolyte containing 1M LiPF6.

[0080] (4) Using a polypropylene separator, the positive electrode, negative electrode and electrolyte prepared above are used to prepare a stacked battery with a capacity of 1.7Ah (the positive electrode, polypropylene separator and negative electrode are stacked in an alternating manner to obtain a stacked cell, and then the cell is placed in an aluminum-plastic film, and after conventional processes such as electrolyte injection and encapsulation, a stacked battery is obtained).

[0081] Examples 2-21 and Comparative Examples 1-4

[0082] The differences between Examples 2-21 and Comparative Examples 1-4 and Example 1 are shown in Table 1; the rest are the same as Example 1.

[0083] The batteries prepared in Examples 1-21 and Comparative Examples 1-4 were tested using the following methods, and the test data are shown in Table 2.

[0084] Test method:

[0085] (1) Discharge DCIR test: At 25℃, charge and discharge at 0.2C to calibrate the battery capacity; charge to 50% SOC at 0.2C, let stand for 30min, set to discharge at 1.5C for 30s, record the termination voltage and termination current of each process, and calculate DCIR; DCIR=(V1-V2) / I, V2 is the voltage after 30s discharge, V1 is the voltage after adjusting the battery to the target SOC and letting stand for 30min, and I is the discharge current.

[0086] (2) DCIR test: At 25℃, charge and discharge at 0.2C to calibrate the battery capacity; charge at 0.2C to 50% SOC, let stand for 30min, set to 1.5C to charge for 30s, record the termination voltage and termination current of each process, and calculate DCIR; DCIR=(V3-V4) / I, V3 is the voltage after charging for 30s, V4 is the voltage after adjusting the battery to the target SOC and letting stand for 30min, and I is the charging current.

[0087] (3) Cyclic performance test: At 25℃, charge and discharge at 0.2C to calibrate the battery capacity C1; conduct charge and discharge test at 1C rate, and the capacity after 200 cycles is C2, and the capacity retention rate = C2 / C1*100%.

[0088] (4) Compaction density test: The negative electrode sheets prepared in each embodiment and comparative example are cut into small circular pieces of a certain size. The weight of the negative electrode dressing in the small circular piece per unit area is measured, and the areal density is calculated (area density = weight of negative electrode dressing / area). The thickness of the negative electrode dressing is also measured. The compaction density is calculated by the areal density of the negative electrode sheet / the thickness of the negative electrode dressing (thickness of negative electrode dressing = electrode sheet thickness - current collector thickness).

[0089] Table 1

[0090]

[0091]

[0092] Table 2

[0093]

[0094]

[0095] As shown in Tables 1 and 2, it can be seen from Examples 1-21 and Comparative Examples 1-4 that by adding MXene material and carbon nanotubes to the electrode and controlling the mass ratio within (0.1-10):1, the DC internal resistance of the examples is lower than that of the comparative examples, the cycle performance after 200 cycles is also better than that of the comparative examples, and the compaction density is better. This shows that the technical solution provided by this application can effectively reduce the battery internal resistance and improve the battery cycle performance and compaction density.

[0096] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. An electrode sheet, characterized in that, The electrode includes a conductive agent, which includes a first conductive agent comprising carbon nanotubes and MXene material, wherein the mass ratio of MXene material to carbon nanotubes is (0.1-10):

1.

2. The electrode sheet according to claim 1, characterized in that, The mass ratio of the MXene material to the carbon nanotubes is (0.2-2):

1.

3. The electrode sheet according to claim 1 or 2, characterized in that, The particle size Dv50 of the MXene material is 0.1μm-5μm.

4. The electrode sheet according to any one of claims 1-3, characterized in that, The general formula of the MXene material is M n+1 X n Tx, where n = 1, 2, 3, M is a transition metal, X is carbon or nitrogen, and Tx is a -O, -F, or -OH group.

5. The electrode sheet according to claim 4, characterized in that, M is at least one of Ti, Zr, Hf, V, Nb, Ta, Cr, Sc, and Mo.

6. The electrode sheet according to any one of claims 1-5, characterized in that, The MXene material includes at least one of Ti3C2Tx, V2CTx, and Nb2CTx.

7. The electrode sheet according to any one of claims 1-6, characterized in that, The thickness L of the MXene material is 1nm-10nm.

8. The electrode sheet according to any one of claims 1-7, characterized in that, The carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

9. The electrode sheet according to any one of claims 1-8, characterized in that, The diameter of the carbon nanotubes is 1nm-40nm.

10. The electrode sheet according to any one of claims 1-9, characterized in that, The conductive agent further includes a second conductive agent, which includes at least one of carbon black, graphene, and carbon fiber materials.

11. The electrode sheet according to any one of claims 1-10, characterized in that, The electrode is a negative electrode.

12. The electrode sheet according to claim 11, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes the conductive agent.

13. The electrode sheet according to claim 12, characterized in that, The negative electrode active layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based negative electrode active material.

14. The electrode sheet according to claim 13, characterized in that, The silicon-based anode active material includes at least one of silicon, silicon alloy, silicon-oxygen material, silicon-carbon material, and silicon-oxygen-carbon material.

15. The electrode sheet according to any one of claims 12-14, characterized in that, The conductive agent accounts for 0.1%-3% of the mass of the negative electrode active layer.

16. The electrode sheet according to any one of claims 12-15, characterized in that, The negative electrode active layer includes a plurality of sub-negative electrode active layers, and at least one of the sub-negative electrode active layers includes the conductive agent.

17. The electrode sheet according to claim 16, characterized in that, The negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer, the second negative electrode active layer being disposed between the negative electrode current collector and the first negative electrode active layer, and the first negative electrode active layer including the conductive agent.

18. The electrode sheet according to claim 17, characterized in that, The conductive agent of the second negative electrode active layer is the second conductive agent and / or the carbon nanotube.

19. The electrode according to claim 18, characterized in that, The porosity of the first negative electrode active layer is greater than that of the second negative electrode active layer.

20. A battery, characterized in that, Includes the electrode sheet as described in any one of claims 1-19.

21. An electrical appliance, characterized in that, Includes the battery as described in claim 20.